Solar-Powered Flood Early Monitoring System with IoT Technology in Parit Raja - Mior Salleh, Meor Amirudin; Telly, Mohammad Jauckry; Zainal Abidin, Zuhairiah; Ghazali, Nurul Bashirah (Multidisciplinary Applied Research and Innovation, 2025)
Flooding is a recurring natural disaster that causes significant damage to infrastructure and poses risks to human lives. This study introduces a solar-powered flood early warning system designed to enhance flood monitoring and management in Parit Raja. The system integrates ultrasonic sensors, water flow sensors, temperature and humidity sensors, and a raindrop sensor with a microcontroller for real-time data collection. Solar panels provide continuous, eco-friendly power, while IoT technologies, including the Blynk application and ESP8266 Wi-Fi module, enable remote monitoring and timely alerts. Testing confirmed the system’s ability to accurately detect water levels and environmental conditions, ensuring reliable performance even under variable weather. The results demonstrate the system’s potential to minimize flood-related risks, reduce property damage, and support proactive response efforts in flood-prone regions. This innovation represents a sustainable and scalable solution for effective flood monitoring and management.